“Optimización del proceso de Envejecimiento en la Perfilería de aluminio en la Empresa Corporación Ecuatoriana de Aluminio s.a Cedal” - Sandoval Jiménez, Carlos Iván (2023)
This thesis work focuses on the optimization of the aging process in aluminum profiles produced by the company Corporación Ecuatoriana de Aluminio S.A Cedal, which aims to reduce the amount of waste of extruded material in the form of aluminum profiles, the latter not having the required hardness, the latter being 7 degrees on the Webster scale as a minimum parameter and a maximum of 10 degrees on the Webster scale. Cedal when making billets of the 6000 series of aluminum, specifically with the 6063 architectural alloy, requires the use of chemical elements such as Silicon, Magnesium and Aluminum. For this purpose, the aging information was collected in order to know its current state and later proceed to elaborate an analysis of the current curve with which Cedal works when submitting the aluminum profiles to heat treatment to obtain hardness. . After knowing the current state of aging, the NTE INEN 2250 standard was analyzed, which details the parameters that the company must comply with when manufacturing the billets, both for their chemical composition and for their hardness.